Treatment of early non-response in patients with schizophrenia: assessing the efficacy of antipsychotic dose escalation. Issue 1 (December 2015) - Loebel, Antony; Citrome, Leslie; Correll, Christoph; Xu, Jane; Cucchiaro, Josephine; Kane, John
Abstract Background Early non-response to antipsychotic treatment in patients with schizophrenia has been shown in multiple studies to predict poor response at short-term trial endpoint. Therefore, strategies to address the challenge of non-improvement early in the course of treatment are needed. A novel trial design was developed to assess the potential utility of antipsychotic dose escalation in patients with an inadequate initial treatment response. This design was embedded in a study intended to assess the efficacy of low dose lurasidone in patients with schizophrenia. The purpose of this report is to describe the background, rationale and design of this study that included a novel method for the assessment of the potential for dose–response in early non-responding patients with schizophrenia. Methods/Design In this 6-week, international, multicenter, double-blind trial, eligible adults with acute schizophrenia were randomized to receive fixed doses of lurasidone 20 mg/day, 80 mg/day (active control), or placebo in a 1:2:1 ratio. Patients initially randomized to lurasidone 80 mg/day who did not have a Positive and Negative Syndrome Scale total score improvement ≥20 % at Week 2 were re-randomized on a 1:1 basis to receive either lurasidone 80 mg/day or lurasidone 160 mg/day for the remainder of the trial. All other groups remained on their initially assigned treatment. The formal primary objective of the study was to evaluate the efficacy of low-dose lurasidone (20 mg/day) compared to placebo; secondary objectives included evaluating the efficacy of lurasidone 80 mg/day versus 160 mg/day in early non-responders, and evaluating the efficacy of lurasidone in all subjects initially randomized to 80 mg/day versus placebo. Discussion Since a lack of early improvement predicts poor response to short-term antipsychotic treatment in patients with schizophrenia, several treatment strategies have been proposed to enhance treatment outcome in early non-responders. A novel clinical trial design involving a placebo arm and re-randomization of early non-responders to increased or maintained antipsychotic dose was developed. The study design described in this report provides a robust method to assess the value of antipsychotic dose escalation in patients with schizophrenia who demonstrate poor initial treatment response. Trial registration ClinicalTrials.govNCT01821378 ; initial registration March 22, 2013